Analysis of Patriarchal Culture in the Consistency of Siri Marriage Practices in Sumenep, Madura: A Socio-Legal and Gender Analysis - Muhammad Nafis; Rofiqi, Insan (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
This research examines the practice of nikah siri in Sumenep District, Madura, using patriarchy theory and legal feminism to analyze gender power relations and structural injustice. Siri marriage - a marriage that is legal in religion but not registered by the state - is influenced by religious, economic and male dominance in decision-making. This study reveals how patriarchal culture legitimizes men’s control over the marriage process, resources and women’s civil rights. Qualitative methods through case studies and in-depth interviews with 25 participants show that 92% of women in siri marriages do not own assets in their own names, while 78% of children face administrative barriers to accessing education. Key findings highlight the legal and economic vulnerabilities experienced by women and children, and the role of religious authorities in maintaining the status quo. This research contributes to the gender discourse by integrating a structural analysis of patriarchy and the legal implications of nikah siri, while offering policy recommendations based on women’s empowerment and cross-sector collaboration. The multidimensional solutions proposed include legal education, marriage registration policy reform and cultural approaches to reduce gender inequality